CYCLISATION-ACETYLATION KINETICOF (R)-(+)-CITRONELLAL BY Zn2+-NATURAL ZEOLITE AS SOLID SOLVENT CATALYST - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2009)
ABSTRACT Kinetic in cyc/isation-acetylation of (R)-(+)-citronellal with acetic anhydride was investigated over Zn2+_ Natural zeolite (Zn2+-Natzeo)as a catalyst. (R)-(+)-citronellalhas been isolated from citronella oil by fractional distillation under reducing pressure. Enantiose/ectivecapillary GC on a Supelco/3-DEX225 column has been used for analysis the enantiomers ratio of citronellal. Catalyst Zn2+-Natzeo has prepared through acid activation of natural zeolite from Malang using HF 1% and HCI 6 M, followed by ion-exchange with 3 M NH4CIand calcination at 450 °C for 1 h under nitrogen to obtainedH-natural zeolite (H-Natzeo). H-Natzeo was modifiedto Zn2+-Natzeoby ion exchange with 0.1 M ZnC/2" Cyclisation-acetylation reaction was carried out by heating (R)-(+)-citronellal (CIT), acetic anhydride (AA), and 1 g catalyst in glass batch reactor with vigorous stirring at 80°C. Molar ratio CIT/AA that used, i.e. 0.25